Public and Private Law Means of Ensuring Economic Security in Russia - Mokhov, Alexandr; Svirin, Yury; Shestov, Sergej; Pеkshev Alexey; Artyukhov, Eduard (Journal of Sustainable Competitive Intelligence, 2025)
Objective: The article aims to examine the public and private law mechanisms that ensure economic security in Russia, with particular attention to the challenges posed by sanctions, geopolitical instability, and the transformation of national economic sovereignty. Methodology/Approach: The study employs general scientific methods of cognition (systemic and theoretical analysis) and specialized legal methods, including comparative jurisprudence, logical and technical-legal analysis, specification, and interpretation. These methods allowed the authors to classify threats to economic security and evaluate the legal measures currently in place. Originality/Relevance: Unlike many existing studies that analyze economic security primarily from a macroeconomic or policy perspective, this research highlights the legal dimension as a decisive factor for sustaining competitiveness and resilience. The paper emphasizes the interaction between state regulation and private sector mechanisms, thereby bridging public and private law. Main Conclusion: Economic security is not limited to protective measures; it also encompasses development, innovation, and the safeguarding of public goods. Legal mechanisms should provide both obligations and incentives for businesses to enhance resilience, supported by sectoral and bankruptcy policies. Theoretical/Methodological Contribution: The article contributes to the theory of economic security by refining the conceptual distinction between threats and risks, integrating them into a legal framework, and demonstrating how legal instruments can strengthen sustainable competitive intelligence in times of crisis.